Heron's cove ebook - Neggers, Carla (Sharpe & Donovan., 2012)
New York Times bestselling author Carla Neggers returns with a gripping story of romantic suspense, where FBI agents Sharpe and Donovan must decide whether working alone or standing together is the only way to outwit an enemy set to tear them apart. When your safety depends on living a lie... After escaping certain death, deep-cover agent Colin Donovan is back home on the Maine coast with his new love, FBI art crimes expert Emma Sharpe. Then Tatiana Pavlova, a London-based jewelry designer, arrives in Heron's Cove, asking for Emma's help--a prized collection from a lost era of Russian opulence, decadence and rare beauty has resurfaced, and Tatiana warns Emma it's about to be stolen again. And Colin realizes his nightmare isn't over. It's just begun. And everyone you love is a target... Emma guards her past closely, and Colin is determined to unlock her secrets. As they investigate the mysterious collection and the equally mysterious Tatiana, they confront their greatest challenge. Now they must count on their expertise--and each other--to outwit an enemy who wants to destroy them and everyone they love most. Who can you afford to trust?